Relationship Between Bird Communities and Environmental Changes in Tandung Village, Tinambung District, Polewali Mandar Regency, West Sulawesi Province - Alexander Kurniawan Sariyanto Putera; Phika Ainnadya Hasan; Muhammad Rizaldi Trias Jaya Putra Nurdin (MANILKARA: Journal of Bioscience, 2023)
Indonesia's coastal region is known for its richness and diverse natural resources. However, the region is experiencing a transformation from mangrove ecosystems to the traditional pond cultures. This was happening in West Sulawesi that could damage the ecosystem in the long term, especially for the bird community. This study aims to inventory bird species in the bird community on the coast of Tandung Village, Tinambung District, Polewali Mandar Regency, West Sulawesi Province. In addition, we also study the bird community structure, find out the correlation among the bird communities, and the environmental condition during the inventory. In this study, we used a fixed-radius point count method to record birds. Field guide titled Burung-burung Pulau Paparan Sunda dan Wallacea di Kepulauan Indonesia was used to identify the species of observed birds. The results showed that of the 27 species recorded, there are 5 species with a high relative abundance, such as Egretta garzetta, Himantopus leucocephalus, Actitis hypoleucos, Ardeola speciosa, and Calidris ruficollis. Only H. leucocephalus is identified as a protected bird by the Indonesian government, while Calidris ruficollis is protected internationally as its conservational status (Near Threatened). The diversity index is moderate level, but it is decreasing day by day of observation, followed by the dominance index, evenness, and species richness. A high correlation between the two bird communities with two adjacent days of observation indicates similarity composition of community structure with different temporal scales and similar spatial scales. The map of environmental conditions shows changing weather in the period of observation sequentially from bright sky to cloudy and heavy rain and back to the normal bright sky at the last period of observation. The response of the bird community to the condition was by flying away when the weather is cloudy and rainy so that may decrease the diversity.